Temperature during vaccination shapes antibody responses and protection against infectious salmon anemia in Atlantic salmon under different prime–boost vaccine strategies - Manuel Soto-Dávila; Shona K. Whyte; Ruth L. Quispe; Yan-Ru Chen; Taylor Wheatley; Shawna L. Semple; Reza Ghanei-Motlagh; Eyesun Fajei; Eleanor Glahn; Frederick von Rönge; Andrew Swanson; Mark D. Fast (Fish & Shellfish Immunology, 2026)

Behavioural thermoregulation segregates sick and healthy fish to enable selective treatment - Massiel F. Copara Chino; Jayoon Lee; Yujin Han; Julia G. Neyedly; Matthew L. Michnik; Patrick Whittaker; Kathryn Smith; Keith B. Tierney; Yamila Carpio; Mario P. Estrada; Mark D. Fast; Brian Dixon; et al. (Aquaculture, 2026)

Ocular Manifestations of Infectious Salmon Anaemia Virus Infection in Atlantic Salmon ( Salmo salar ) - Emily Mahon; Rebecca R. Kwabiah; Hélène Paradis; Manuel A. Soto‐Dávila; Sathees Duglas; Raja Ram Gurung; Thurka Paramanathan; Ignacio Vasquez; Shams Al‐Badoosh; John Law; Javier Santander; Mark D. Fast; et al. (Journal of Fish Diseases, 2026)
Eyes are essential sensory organs needed by teleost Atlantic salmon for high visual acuity and survival in both the wild and in aquaculture settings. In this work, we assessed the ocular manifestations of Infectious Salmon Anaemia Virus (ISAV) infection in Atlantic salmon by a cohabitation‐mediated infection assay and histological and immunohistochemical approaches. The findings reveal that Atlantic salmon with a systemic ISAV infection displayed ISAV antigen accumulation in specific ocular tissues and significant ocular morphological changes that could compromise visual acuity. Immunohistochemical analyses showed that ISAV‐related ocular pathological changes correlate with changes in expression levels and/or spatial localizations of IgM, Sox6, Sox9, collagen type 1, Gata1, and CD10 in specific compartments of the eye. The cornea is likely one of the first ocular tissues to be exposed to the cohabitation‐mediated ISAV infection. The ISAV‐infected Atlantic salmon showed corneal dysplasia, which correlated with increased corneal stromal ISAV antigen expression, dysregulated IgM, Sox6, and collagen type 1 expression, and an induction of Sox9 expression at the corneal surface. The choroid rete mirabile of ISAV‐infected eyes showed a decreased complement of erythrocytes, consistent with anaemia, while Gata1 expression, a key mediator of erythropoiesis, was upregulated compared to non‐infected eyes, suggesting a potential erythropoietic compensatory response. These findings provide a basis for further study of ISAV‐mediated ocular pathological changes and new insight into the pathogenesis of orthomyxoviruses in the eye.

Investigation of a novel assay for the proteomic screening of the secretory and excretory products of individual salmon lice Lepeophtheirus salmonis - Alexander Dindial; James E. Bron; Michael McGowan; Ava Drake; Kevin McLean; Dorota Androscuk; William Roy; Andre Van; Diego Robledo; Richard Paley; Claire Joiner; Mark D. Fast; et al. (Veterinary Parasitology, 2026)

Effects of two natural astaxanthin products derived from the green microalga Haematococcus lacustris on production parameters and fillet quality of Atlantic salmon (Salmo salar) - Juan A. Manríquez-Hernández; Sean M. Tibbetts; Mark D. Fast; Stacey R. Goldberg; Roumiana Stefanova; Stefanie M. Colombo (Aquaculture International, 2025)

Local inflammation at the salmon louse (Lepeophtheirus salmonis) attachment site contributes to copepodid rejection in coho salmon (Oncorhynchus kisutch) - Lene Sveen; Mark D. Fast; Torstein Tengs; Rachel A. Kline; Judit Aguilar Marti; Dominic Kurian; Gerrit Timmerhaus; Marianne Vaadal; Ross D. Houston; James E. Bron; Sean J. Monaghan; Haitham H. Mohammed; et al. (Cell and Tissue Research, 2025)
The study investigates the susceptibility of Atlantic salmon ( Salmo salar ) and Pacific salmon species (pink salmon, Oncorhynchus gorbuscha ; coho salmon, Oncorhynchus kisutch ; and chum salmon, Oncorhynchus keta ) to the parasitic salmon lice ( Lepeophtheirus salmonis ). The research had two main objectives: to characterize the morphology of the scaly skin in four salmonid species and to compare the cellular response at the louse attachment site in coho salmon and Atlantic salmon. Three consecutive challenge trials were conducted, with successful louse infestation only achieved across all four species in the third trial using mild anesthesia with tricaine methanesulfonate. Skin and fin samples were collected at 12, 24, 36, 48, 60, and 168 h post-infestation (hpi) for histological, proteomic, and spatial transcriptomic analyses. Results showed that chum salmon had significantly higher mucous cell coverage (30–40%) in the epithelium of scaly skin compared to Atlantic salmon (10%). At the louse attachment site in coho salmon, there was a greater influx of inflammatory cells at 36–48 hpi compared to Atlantic salmon. Proteomic analysis at 12 hpi and 36 hpi in coho salmon showed upregulation of neutrophil degranulation and formyl-methionyl-leucyl-phenylalanine signaling. Additionally, spatial transcriptomics at the attachment site showed local upregulation of inflammatory gene markers. These findings suggest that coho salmon mount a rapid and large-scale inflammatory response driven by neutrophils to louse attachment within the first 48 hpi. Overall, the study emphasizes the significance of local changes at the host-parasite interface for resistance mechanisms against salmon lice.

Morphology and molecular phylogeny of Rhadinorhynchus nudus (Harada, 1938) (Acanthocephala: Rhadinorhynchidae) from Euthynnus affinis (Scombridae) in the Persian Gulf off Iran - Reza Ghanei-Motlagh; Jesús S. Hernández-Orts; Mark D. Fast; Mansour El-Matbouli; Mona Saleh (Systematic Parasitology, 2025)

Synergies of co-infecting pathogens, sea lice (Lepeophetheirus salmonis) and Moritella viscosa, are impacted by exposure order, and host response to initial infection - Wenlong Cai; Liang Zhong; Kathleen Parrish; Surendra Kumar; Khalil Eslamloo; Eyesun Fajei; Shona K. Whyte; Sara L. Purcell; Ladan Jahangiri; Runsheng Li; Albert Caballero Solares; Richard G. Taylor; et al. (Aquaculture, 2024)

Characterization of the impact of dietary immunostimulant CpG on the expression of mRNA biomarkers involved in the immune responses in Atlantic salmon (Salmo salar) - Xi Xue; Khalil Eslamloo; Albert Caballero-Solares; Tomer Katan; Navaneethaiyer Umasuthan; Richard G. Taylor; Mark D. Fast; Rune Andreassen; Matthew L. Rise (Fish & Shellfish Immunology, 2024)

An aquaculture risk model to understand the causes and consequences of Atlantic Salmon mass mortality events: A review - Zaman Sajid; A. Kurt Gamperl; Christopher C. Parrish; Stefanie M. Colombo; Javier Santander; Charles Mather; Barbara Neis; Ingunn Marie Holmen; Ramón Filgueira; Cynthia H. McKenzie; Lissandra Souto Cavalli; Mohamed Jeebhay; et al. (Reviews in Aquaculture, 2024)
Mass mortality events (MMEs) are defined as the death of large numbers of fish over a short period of time. These events can result in catastrophic losses to the Atlantic salmon aquaculture industry and the local economy. However, they are challenging to understand because of their relative infrequency and the high number of potential factors involved. As a result, the causes and consequences of MMEs in Atlantic salmon aquaculture are not well understood. In this study, we developed a structural network of causal risk factors for MMEs for aquaculture and the communities that depend on Atlantic salmon aquaculture. Using the Interpretive Structural Modeling (ISM) technique, we analysed the causes of Atlantic salmon mass mortalities due to environmental (abiotic), biological (biotic) and nutritional risk factors. The consequences of MMEs were also assessed for the occupational health and safety of aquaculture workers and their implications for the livelihoods of local communities. This structural network deepens our understanding of MMEs and points to management actions and interventions that can help mitigate mass mortalities. MMEs are typically not the result of a single risk factor but are caused by the systematic interaction of risk factors related to the environment, fish diseases, feeding/nutrition and cage‐site management. Results also indicate that considerations of health and safety risk, through pre‐ and post‐event risk assessments, may help to minimize workplace injuries and eliminate potential risks of human fatalities. Company and government‐assisted socio‐economic measures could help mitigate post‐mass mortality impacts. Appropriate and timely management actions may help reduce MMEs at Atlantic salmon cage sites and minimize the physical and social vulnerabilities of workers and local communities.

A comparative analysis of alternative splicing patterns in Atlantic salmon (Salmo salar) in response to Moritella viscosa and sea lice (Lepeophtheirus salmonis) infection - Shengnan Gao; Suxu Tan; Sara L. Purcell; Shona K. Whyte; Kathleen Parrish; Liang Zhong; Shucheng Zheng; Yuxuan Zhang; Ruoxi Zhu; Ladan Jahangiri; Runsheng Li; Mark D. Fast; et al. (Fish & Shellfish Immunology, 2024)

Transcriptome analysis revealed immune responses in the kidney of Atlantic salmon (Salmo salar) co-infected with sea lice (Lepeophtheirus salmonis) and infectious salmon anemia virus - Liang Zhong; Laura A. Carvalho; Shengnan Gao; Shona K. Whyte; Sara L. Purcell; Mark D. Fast; Wenlong Cai (Fish & Shellfish Immunology, 2023)

Characterizing host-pathogen interactions between Zostera marina and Labyrinthula zosterae - Yaamini R. Venkataraman; Amanda Shore; Sukanya Dayal; James Sanghyun Lee; Mahsa Alidoost Salimi; Grace Crandall; Malina M. Loeher; Mark Stoops; Megan Swanger; Morgan E. Eisenlord; Kathryn L. Van Alstyne; Mark D. Fast; et al. (Frontiers in Marine Science, 2023)
Introduction Seagrass meadows serve as an integral component of coastal ecosystems but are declining rapidly due to numerous anthropogenic stressors including climate change. Eelgrass wasting disease, caused by opportunistic Labyrinthula spp., is an increasing concern with rising seawater temperature. To better understand the host-pathogen interaction, we paired whole organism physiological assays with dual transcriptomic analysis of the infected host and parasite. Methods Eelgrass ( Zostera marina ) shoots were placed in one of two temperature treatments, 11° C or 18° C, acclimated for 10 days, and exposed to a waterborne inoculation containing infectious Labyrinthula zosterae ( Lz ) or sterile seawater. At two- and five-days post-exposure, pathogen load, visible disease signs, whole leaf phenolic content, and both host- and pathogen- transcriptomes were characterized. Results Two days after exposure, more than 90% of plants had visible lesions and Lz DNA was detectable in 100% percent of sampled plants in the Lz exposed treatment. Concentrations of total phenolic compounds were lower after 5 days of combined exposure to warmer temperatures and Lz , but were unaffected in other treatments. Concentrations of condensed tannins were not affected by Lz or temperature, and did not change over time. Analysis of the eelgrass transcriptome revealed 540 differentially expressed genes in response to Lz exposure, but not temperature. Lz -exposed plants had gene expression patterns consistent with increased defense responses through altered regulation of phytohormone biosynthesis, stress response, and immune function pathways. Analysis of the pathogen transcriptome revealed up-regulation of genes potentially involved in breakdown of host defense, chemotaxis, phagocytosis, and metabolism. Discussion The lack of a significant temperature signal was unexpected but suggests a more pronounced physiological response to Lz infection as compared to temperature. Pre-acclimation of eelgrass plants to the temperature treatments may have contributed to the limited physiological responses to temperature. Collectively, these data characterize a widespread physiological response to pathogen attack and demonstrate the value of paired transcriptomics to understand infections in a host-pathogen system.

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

Estimating the dispersal of Lepeophtheirus salmonis sea lice within and among Atlantic salmon sites of the Bay of Fundy, New Brunswick - Marianne I. Parent; Henrik Stryhn; K. Larry Hammell; Mark D. Fast; Jon Grant; Raphaël Vanderstichel (Journal of Fish Diseases, 2021)
The objective of this study was to estimate the impact of infestation pressures on the abundance of the parasitic sea louse, Lepeophtheirus salmonis , in the Bay of Fundy, New Brunswick (NB), Canada, using the Fish‐iTrends database for the years 2009–2018. Infestation pressures were calculated as time‐lagged weighted averages of the abundance of adult female (AF) sea lice within a site (internal infestation pressure: IIP) and among sites (external infestation pressure: EIP). The EIP weights were calculated from seaway distances among sites and a Gaussian kernel density for bandwidths of 5 to 60 km. The EIP with a bandwidth of 10 km had the best fit, as determined with Akaike's information criterion, and historical AF sea lice abundance. This estimated dispersal distance of 10 km was similar to previous studies in Norway, Scotland and in New Brunswick. The infestation pressures estimated from empirical AF sea lice abundance within and among sites significantly increased the abundance of AF sea lice ( p

Hydrogen peroxide treatment and its impacts on Lepeophtheirus salmonis originating from the Bay of Fundy, Canada - Carter R. VanIderstine; Jordan D. Poley; Shona K. Whyte; Sara L. Purcell; Mark D. Fast (Journal of Fish Diseases, 2021)
Hydrogen peroxide (H 2 O 2 ) is used to treat sea lice infections of farmed salmonids in the Atlantic and Pacific Oceans and issues with resistance to this treatment, and others are a major threat to the sustainability of the industry. The objectives of this study were to determine how H 2 O 2 exposure affects survival and antioxidant‐related gene expression in salmon lice ( Lepeophtheirus salmonis ) collected from the Bay of Fundy, New Brunswick. The maximum recommended dose of H 2 O 2 is 1,800 mg/L, while the EC 50 values (with 95% CI) for the population tested were 1,486 (457, 2,515) mg/L for males and 2,126 (984, 3,268) mg/L for females. Neither temperature nor pretreatment with emamectin benzoate (EMB) impacted survival after H 2 O 2 exposure. RT‐qPCR was performed on pre‐adult sea lice exposed to H 2 O 2 and showed that four genes classically involved in the response to oxidative stress were unchanged between treated and control groups. Seven genes were found to be significantly upregulated in males and one in females. This is the first report on the efficacy and molecular responses of Atlantic Canada sea lice to H 2 O 2 treatment.

Impact of co‐infection with Lepeophtheirus salmonis and Moritella viscosa on inflammatory and immune responses of Atlantic salmon ( Salmo salar ) - Laura A. Carvalho; Shona K. Whyte; Laura M. Braden; Sara L. Purcell; Anthony J. Manning; Anne Muckle; Mark D. Fast (Journal of Fish Diseases, 2020)
This study was conducted to determine the effects of a co‐infection with Moritella viscosa at different exposure levels of sea lice Lepeophtheirus salmonis in Atlantic salmon ( Salmo salar ). M. viscosa (1.14 × 10 6 cfu/ml) was introduced to all experimental tanks at 10 days post‐lice infection (dpLs). Mean lice counts decreased over time in both the medium lice co‐infection (31.5 ± 19.0 at 7 dpLs; 16.9 ± 9.3 at 46 dpLs) and high lice co‐infection (62.0 ± 10.8 at 7 dpLs; 37.6 ± 11.3 at 46 dpLs). There were significantly higher mortalities and more severe skin lesions in the high lice co‐infected group compared to medium lice co‐infected group or M. viscosa ‐only infection. Quantitative gene expression analysis detected a significant upregulation of genes in skin from the high lice co‐infection group consistent with severe inflammation ( il‐8 , mmp‐9 , hep, saa ). Skin lesions retrieved throughout the study were positive for M. viscosa growth, but these were rarely located in regions associated with lice. These results suggest that while M. viscosa infection itself may induce skin lesion development in salmon, co‐infection with high numbers of lice can enhance this impact and significantly reduce the ability of these lesions to resolve, resulting in increased mortality.

Cover Image - Laura A. Carvalho; Shona K. Whyte; Laura M. Braden; Sara L. Purcell; Anthony J. Manning; Anne Muckle; Mark D. Fast (Journal of Fish Diseases, 2020)

A genetic linkage map for the salmon louse (Lepeophtheirus salmonis): evidence for high male:female and inter-familial recombination rate differences - Roy G. Danzmann; Joseph D. Norman; Eric B. Rondeau; Amber M. Messmer; Matthew P. Kent; Sigbjørn Lien; Okechukwu Igboeli; Mark D. Fast; Ben F. Koop (Molecular Genetics and Genomics, 2019)

Copper Alters the Effect of Temperature on Mitochondrial Bioenergetics in Rainbow Trout, Oncorhynchus mykiss - Ravinder Sappal; Michelle MacDougald; Don Stevens; Mark D. Fast; Collins Kamunde (Archives of Environmental Contamination and Toxicology, 2014)